PENGEMBANGAN NILAI TAMBAH KOMODITAS PERTANIAN DI KECAMATAN SIMPANG EMPAT KABUPATEN KARO - Napitupulu, Runggu Besmandala; Hutabarat, Lamminar; Silaen, Novia Ruth; Tarigan, Jenni; Elly Ria, Chainar (PKM Maju UDA, 2024)
Community service outreach activities aim to increase insight into the added value development of agricultural commodities, especially carrots, red chilies and sweet oranges in Simpang Empat sub-district, Karo district; Improvement of inadequate attributes and development of new attributes so that agricultural products have higher market value; Increasing farmers' innovation capabilities in relation to the supply chain in order to increase added value. The presentation was held in the meeting room of the sub-district office which was attended by 30 (thirty) participants. The concepts expressed concern innovation capabilities, building competitive advantage through rare resources, vision and mission formulation and internalization, and supply chain management. The result was a change in farmers' work techniques. Farming communities are increasingly selling their agricultural products in the farms. There are farmers efforts to improve their agricultural performance either by shortening the supply chain or packaging so that it is safer and more attractive.